2021
DOI: 10.1111/tbed.14149
|View full text |Cite
|
Sign up to set email alerts
|

Detection and genetic analysis of a novel atypical porcine pestivirus from piglets with congenital tremor in Japan

Abstract: Atypical porcine pestivirus (APPV), which has been confirmed to be associated with congenital tremor (CT) in pigs, is a newly discovered porcine virus that has been found in the Americas, Europe and Asia; however, no report of APPV in Japan has been published. We identified an APPV in the central nervous system of Japanese piglets with CT and firstly determined and analysed the complete genome sequence. Phylogenetic analysis using the complete genome nucleotide sequence of the Japanese APPV, named Anna/2020, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
7
1
1
Order By: Relevance
“…We found a strong association between phylogeny and geographic trait (Table 1), revealing geography-driven adaptation as an important factor for the diversification of APPV. Actually, this scenario has been supposed in a recent study from Japan, in which APPVs may independently evolve in the Japanese pig population (Kasahara-Kamiie et al, 2021). In addition, we failed to find recombination signals in the E2 region in our study, although previous works have revealed the presence of recombination events in the non-structural gene regions (Guo et al, 2020).…”
Section: Discussioncontrasting
confidence: 57%
“…We found a strong association between phylogeny and geographic trait (Table 1), revealing geography-driven adaptation as an important factor for the diversification of APPV. Actually, this scenario has been supposed in a recent study from Japan, in which APPVs may independently evolve in the Japanese pig population (Kasahara-Kamiie et al, 2021). In addition, we failed to find recombination signals in the E2 region in our study, although previous works have revealed the presence of recombination events in the non-structural gene regions (Guo et al, 2020).…”
Section: Discussioncontrasting
confidence: 57%
“…APPV has been found in North America, South America, Europe, and Asia thus far ( 6 ). Furthermore, it has been classified into three genotypes, i.e., genotype 1, genotype 2, and genotype 3 ( 7 ). APPV strains classified as genotype 3 were mostly detected in China ( 7 ).…”
Section: Announcementmentioning
confidence: 99%
“…Furthermore, it has been classified into three genotypes, i.e., genotype 1, genotype 2, and genotype 3 ( 7 ). APPV strains classified as genotype 3 were mostly detected in China ( 7 ). Kasahara-Kamiie et al recently reported a novel APPV strain belonging to genotype 3, speculating that it might have evolved uniquely in the Japanese pig population ( 7 ).…”
Section: Announcementmentioning
confidence: 99%
See 2 more Smart Citations